Analysis of Profit Management and Financial Performance of the Acquiring Companies Before and After Mergers and Acquisitions Listed on the Indonesia Stock Exchange, 2018-2019 - Winarno Winarno; Hendra Yuharmain H.; Annisa Annisa (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this study was to obtain empirical evidence of whether the acquirer conduct earnings management prior to the implementation of mergers and acquisitions. Also aims to determine changes in the acquirer's financial performance before and after mergers and acquisitions. Earnings management by firms is to proxy discretionary accrual (DA). Then for the measurement of company performance measured by financial ratios include total asset turn over, net provit margin,and return on asset. The analysis was done by using independent sample t-test and paired sample test. The results shows that there is an indication of earnings management done by taking over companies before mergers and acquisitions by utilizing income increasing accruals. Furthermore, the company's financial performance as measured by total asset turnover ratio has increased after the merger and acquisition, while net profit margin and return on assets has decreased after the mergers and acquisitions.